The influence of inorganic admixtures on early cement hydration from the point of view of thermodynamics. (30th October 2020) - Chen, Heng; Feng, Pan; Ye, Shaoxiong; Li, Qinfei; Hou, Pengkun; Cheng, Xin
Highlights: Calorimetric curves of cement with inorganic admixtures were analyzed quantitatively. Thermodynamic analysis of hydration of the cement with the admixtures was investigated. Hydration rate were quantitatively correlated to saturation index of relevant phases. Calcium concentration plays a key role in the evolution of saturation index of relevant phases. Abstract: Calcium salt and other inorganic chemicals have long been used as the accelerators of cement hydration; however, the underlying mechanism remains to be resolved. In this contribution, thermodynamic analysis of cement systems with calcium chloride (0.06 M and 0.12 M), potassium hydroxide (0.28 M and 0.56 M) and hydrochloric acid (0.09 M and 0.18 M) were combined with quantitative analysis of the calorimetric curves of these systems. Calorimetric tests show that calcium chloride and hydrochloric acid would increase hydration rate, whereas lower dosage of potassium hydroxide would decrease hydration rate. Thermodynamic analyses show that in all the systems, the chemical driving force of C3 S dissolution keeps increasing whereas that of calcium silicate hydrates (C-S-H) precipitation keeps decreasing, indicating that the dissolution of C3 S could be the limiting step of cement hydration. This is further confirmed by the facts that the chemical driving force of tricalcium silicate (C3 S) dissolution is positively related to both the intensity of the silicate peak and the occurring time of the silicate peak time, and that the chemical driving force of C3 S dissolution is negatively related to the length of induction period. Furthermore, the calcium concentration of pore solution is positively related to the chemical driving force of C3 S dissolution, implying that calcium concentration could play a critical role in regulating effect of inorganic admixtures. This work finds the crucial role of C3 S dissolution in early cement hydration and also provides new insight into the effect of inorganic chemicals on cement hydration and the mechanism of cement hydration.